Relační a NoSQL databáze pro sběr dat z IoT zařízení - Tomiczek, Roman (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2018)
Bakalářská práce se zabývá analýzou relační a NoSQL (Not only SQL) databází pro sběr velkého množství dat z IoT (Internet of Things) zařízení. Teoretická část obsahuje seznámení se s relační a NoSQL databází. U relační databáze popisuje základní principy, relační algebru, normální formy atd. U nerelační databáze charakterizuje základní vlastnosti a popisuje různé typologie. Přiblíží také NoSQL dokumentovou databázi Elasticsearch. Praktická část obsahuje návrh a realizaci databáze MySQL, realizaci nerelační databáze Elasticsearch a JavaFx aplikaci pro měření parametrů databáze. Dále obsahuje výsledky měření parametrů a vlastností databází.

This bachelor work is focused on the analysis of the relational and NoSQL (Not only SQL) databases for collecting a huge amount of data from IoT (Internet of Things) device. Theoretical part contains an introduction to the problematic of the relational and NoSQL databases. The relational database describes fundamental principles, relational algebra, normal forms and so on. The non-relational database characterises the main properties and describes different types of typologies. It deals with the NoSQL documentation databases called Elasticsearch as well. Practical part contains a proposal and realization of the MySQL database, realization non-relational database Elasticsearch as well as JavaFx application for measurement of database parameters. Further contains results of the measurement of parameters and properties of databases.
Relational and NoSQL database for collecting data from IoT devices
Keywords: Databáze; MySQL; NoSQL; Elasticsearch; Java; Database; MySQL; NoSQL; Elasticsearch; Java